An Honourable Profession: Public Employees and Identity Construction in Chile, 1880–1920 - Barria-Traverso, D (Blackwell Publishing Ltd, 2019)
This paper analyses how public employees at two Chilean government offices constructed their occupational identities. In contrast to the vast majority of previous work, which took the 1920s as its starting point, this study focuses on the period between 1880 and 1920. Additionally, the construction of identity is analysed in direct relation to performance in the workplace. The paper asserts that public criticism of their performance prompted public employees to develop an image of themselves based on the concept of their honourability as competent and honest workers. © 2018 The Author. Bulletin of Latin American Research © 2018 Society for Latin American Studies. Published by John Wiley & Sons Ltd